Methicillin resistance and the biofilm phenotype in Staphylococcus aureus - McCarthy, Hannah; Rudkin, Justine K.; Black, Nikki S.; Gallagher, Laura; O'Neill, Eoghan; O'Gara, James P. (Frontiers in Cellular and Infection Microbiology, 2015)
Antibiotic resistance and biofilm-forming capacity contribute to the success of Staphylococcus aureus as a human pathogen in both healthcare and community settings. These virulence factors do not function independently of each other and the biofilm phenotype expressed by clinical isolates of S. aureus is influenced by acquisition of the methicillin resistance gene mecA. Methicillin-sensitive S. aureus (MSSA) strains commonly produce an icaADBC operon-encoded polysaccharide intercellular adhesin (PIA)-dependent biofilm. In contrast, the release of extracellular DNA and cell surface expression of a number of sortase-anchored proteins, and the major autolysin have been implicated in the biofilm phenotype of methicillin-resistant S. aureus (MRSA) isolates. Expression of high level methicillin resistance in a laboratory MSSA strain resulted in i) repression of PIA-mediated biofilm production, ii) down-regulation of the accessory gene regulator (Agr) system and iii) attenuation of virulence in murine sepsis and device infection models. Here we review the mechanisms of MSSA and MRSA biofilm production and the relationships between antibiotic resistance, biofilm and virulence gene regulation in S. aureus.